Evaluations of psychosocial cancer support services: A scoping review. - Solveigh P Lingens; Holger Schulz; Christiane Bleich (PLoS ONE)
Background A diagnosis of cancer leaves most patients with cancer and their relatives with an increased psychological burden. Throughout the course of the illness, social, occupational or legal changes may lead to psychological distress. Psychosocial cancer support services offer psychological, social and legal support. However, little is known about the effectiveness of psychosocial support services implemented in health care. Therefore, this scoping review aims to provide an overview of current literature evaluating out-patient psychosocial support services. Methods Databases searched were PubMed, PsycINFO, PSYNDEX, PsycArticle, Medline, Web of Science, Google Scholar, Cochrane, and Embase. Two independent researchers conducted the systematic search. We included studies that were published in English and assessed at least one patient reported outcome measure. Studies that assessed psychotherapy, online support or telephone counselling were excluded. The review was reported according to PRISMA-ScR guidelines. A search of the databases identified 2104 articles. After excluding duplicates, screening titles, abstracts and full-texts, 12 studies matching the criteria were identified. Results One study was an RCT, six were prospective with no control group and five studies were cross-sectional with one measurement point. The most common outcome measures across studies were well-being, concerns and satisfaction with the support services. Conclusion While the included studies indicate some improvements to well-being for patients with cancer, the low number and lack of high quality of studies indicate these findings should be interpreted with caution. However, high-quality research on the effectiveness of psychosocial support services is needed to determine that the interventions are effective.